Interrogating gender constructions in the Daily Sun: an analysis of the coverage of the 'Charter for a Man' campaign against gender violence between November and December 2007 - Dewa, Nonhlanhla (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2009)
The study seeks to interrogate the gender constructions in the Daily Sun's "Charter for a Man" campaign which ran from 7 November to 7 December 2007. It coincided with the 16 Days of Activism against gender violence and was designed to lobby support for this campaign and discourage men from physically abusing women. The "Charter for a Man" listed nine principles that signatories were to abide by. It included a section to be signed by men to be submitted to and collected by the Daily Sun. The campaign was constructed as an intervention into the issue of gender violence. Consequently, the 30 news stories, four editorial pieces and 11 letters to the editor that were published during the campaign period make up the textual data analysed in the study. The news stories consisted of testimonies from abused women and some women abusers. In addition, celebrity signatories were selected to endorse the campaign and encourage other men to follow suit. In the editorials, the campaign was consistently flagged as a nation building initiative which all men were supposed to support. The letters to the editor consisted of readers who either supported or rejected the campaign. The study takes place against the context of a patriarchal society characterised by high levels of violence. Given this scenario, the study is informed by a concern with gender justice and therefore considers whether such a campaign, ostensibly aimed at eradicating gender violence, has the potential of being transformative of gender inequalities. The study set out to establish the kinds of masculinities and femininities that were variously constituted in the campaign as well as the gender discourses that were privileged. It is informed by the theories of feminist poststructuralism and Foucault's conceptualisation of discourse. As the campaign is the initiative of a tabloid newspaper, it is also considered within the framework of newspaper campaigns and arguments about tabloids and the public sphere. As text based research, the study employs critical discourse analysis as a qualitative procedure of textual analysis. It makes use of an eclectic approach to textual analysis that draws on linguistics, narrative and argumentation. The texts are analysed according to the categories of news texts contained which includes the Charter itself, signatory articles, testimonies, vox pops and letters to the editor. The overarching theme of nationhood projected in the editorials and other categories is also discussed as part of the analysis. The study concludes that the Daily Sun campaign might be a seemingly progressive action at first glance. However, it does not challenge the existing gender order but rather maintains and sustains patriarchal attitudes through the repeated representation of women as weak and in need of patronage and men as their protectors and providers. In some instances, women are constructed primarily as sexual beings as their physical attributes are emphasised, while men are constructed as working class citizens and rational beings. The study therefore proposes that the Daily Sun fails as an alternative public sphere that might make visible the concerns of women as a marginalised group in society. The campaign, it is argued, is self-serving in its promotion of the Daily Sun's image as the "People's Paper" rather than serious concerns about gender violence.
Keywords: Foucault, Michel, 1926-1984 -- Criticism and interpretation; Daily Sun; Women -- Violence against; Mass media and women; Abused women; Tabloid newspapers; Discourse analysis